KEARIFAN LOKAL TRADISI NYADRAN LINTAS AGAMA DI DESA KAYEN-JUWANGI KABUPATEN BOYOLALI Local Wisdom of Cross-Religious Nyadran Tradition at Kayen-Juwangi Village of Boyolali - Agus Riyadi (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
Culture and local tradition, a representation of local knowledge or local wisdom serve as a means of cultural accommodation to maintain the harmonious environment situation, including social relationships of cross-religious life and even across cultures. One of the local wisdom values in community is the ritual Nyadran tradition. This study is intended to reveal how the Nyadran tradition can accommodate cross-religious relationships in the Kayen village, Jemangi- Boyolali. This research uses qualitative approach. The important research findings are that Nyadran tradition can be an expression of social piety through the practice of mutual cooperation, solidarity, and togetherness. Nyadran can be a medium of accommodation and building harmony among people, especially in plural and multicultural community. The tradition in Kayen village with its various procedures has been able to develop the primordial ties of its community in a group that share the same views and beliefs despite their different religions and beliefs.